Socio-Historical Study of Islamic Spiritual Institutions: Tasawuf and Tarekat Archipelago - Hamidah, Hamidah; Akhyar, Taufik; Choiriyah, Choiriyah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
This article aimed to analyse this study is important and strategic to examine socio-historically the spiritual institutions of Islam: Sufism and tarekat that developed in the archipelago. The three main focus in this research are: (1). To find out how the concept of Islamic Spiritual Institutions (Sufism and tarekat) (2). To find out the historical background of Islamic Spiritual Institutions (3). To find out the development of Islamic Spiritual Institutions in the Sociological Perspective. The research method used is qualitative method with sociological approach and historical approach. The study of Development of Islamic Spiritual Institutions: Studies of Sufism and the Congregation in a Sociological Perspective was carried out with library research that sought to explore data collected through literature from various sources; books, newspapers, journals about interactions between individuals and other individuals adhering to certain tarekat related to the problem discussed. subject matter so that the data obtained from the literature can be inventoryed. The final results showed that the spread of Islam in the archipelago cannot be separated from Sufism. Even the "First Islam" which was internalized in the archipelago is actually Islam spread with Sufism. The spreaders of Islam in Indonesia are generally to Da'is who have knowledge and practice of Sufism. Among them are also many who become pangamal and spreaders of tarekat in Indonesia.